ANALISIS KEMAMPUAN NUMBER SENSE SISWA KELAS V SD SEKECAMATAN TAMPAN PEKANBARU - Nurhanida '; Gustimal Witri; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The ability of number sense is as one indicator of the success to learn mathematics. So far, many study math on numbers just focus on learning outcomes. Therefore, based on the problems need to investigate students ability of number sense. The intention of the present study is to identify and analyze number sense ability of fifth graders in Tampan district Pekanbaru. Population in this study are 3,142 students and sample are 275 students, taken by cluster random sampling which represent each cluster in Tampan District. This research is descriptive quantitative research. The method used in this research is survey method with data collection techniques using test consisting of 20 questions that have been validated by experts and small groups. The results showed that number sense of students are low with percentage is 49,88%, especially in deciding wisely from the calculation through different strategies.Keywords: Number sense